The mechanism of assortative mating for educational attainment: a study of Finnish and Dutch twins and their spouses - Gonggrijp, Bodine M. A.; Silventoinen, Karri; Dolan, Conor V.; Boomsma, Dorret I.; Kaprio, Jaakko; Willemsen, Gonneke (Frontiers in Genetics, 2023)
Introduction: Assortative mating refers describes a phenomenon in which individuals with similar phenotypic traits are more likely to mate and reproduce with each other; i.e. assortative mating occurs when individuals choose partners based on their similarity or dissimilarity in certain traits.to patterns of non-random mating of spouses leading to phenotypic resemblance. There are various theories about the its underlying mechanisms, which have different genetic consequences. Methods: We analyzed examined two possible mechanisms underlying assortative mating – phenotypic assortment and social homogamy – for educational attainment in two countries utilizing data of mono- and dizygotic twins and their spouses (1,451 Finnish and 1,616 Dutch twin-spouse pairs). Results: The spousal correlations were 0.51 in Finland and 0.45 in the Netherlands, to which phenotypic assortment contributed 0.35 and 0.30, and social homogamy 0.16 and 0.15, respectively. Conclusion: Both social homogamy and phenotypic assortment are important processes in spouse selection in Finland and the Netherlands. In both countries, phenotypic assortment contributes to a greater degree to the similarity of spouses than social homogamy.